Inositol Inclusion Affects Growth, Body Composition, Antioxidant Performance, and Lipid Metabolism of Largemouth Bass (Micropterus salmoides) - Yinglin Xu; Ye Gong; Songlin Li; Yue Zhou; Zhixiao Ma; Ganfeng Yi; Naisong Chen; Weilong Wang; Xuxiong Huang (Aquaculture Nutrition, 2024)
The present study explored the effects of inositol on growth performance, body composition, antioxidant performance, and lipid metabolism of largemouth bass (Micropterus salmoides). Six isonitrogenous and isolipidic diets containing 0 mg/kg (G1, control), 125 mg/kg (G2), 250 mg/kg (G3), 375 mg/kg (G4), 500 mg/kg (G5), and 625 mg/kg (G6) inositol were prepared and fed to cultured fish (initial weight: 110 ± 1 g) for 8 weeks in recirculating the aquaculture systems. The results indicated that compared with G1 group, the weight gain rate (WGR), specific growth rate (SGR), and feed efficiency rate (FER) in the G3 group were significantly higher. The crude lipid content of the whole fish and the liver of cultured fish was significantly reduced with increasing dietary inositol inclusion. However, no significant effects on moisture, crude protein, and ash contents of fish were observed among the different groups. Dietary inositol supplementation significantly increased muscular crude protein. However, muscular total lipid contents were decreased when the inclusion level was higher than 250 mg/kg (G3–G6 groups). As dietary inositol supplemental level increased, serum triglyceride (TG), and cholesterol (TC) contents showed an increasing trend and reached the maximum value in the G3 group. Additionally, serum low-density lipoprotein cholesterol (LDL-C) in G2, G3, G4, and G5 groups was significantly upregulated by increasing inositol. While, there was no significant change in serum high-density lipoprotein cholesterol (HDL-C) among the treatments. Inositol inclusion also significantly reduced the serum alkaline phosphatase (AKP), glutamic–pyruvic transaminase (ALT), and glutamic–oxaloacetic transaminase (AST) activities as well as serum malondialdehyde (MDA) content but significantly increased serum catalase (CAT), superoxide dismutase (SOD) activities, and total antioxidant capacity (T-AOC). Compared with the control group, the activities of hepatic total lipase (TL) and lipoprotein lipase (LPL) were significantly elevated in the G3, G4, and G5 groups. Above all, dietary inositol supplementation could improve growth performance and antioxidant capacity, and reduce the liver fat content of largemouth bass, and the optimal supplementation level of inositol in feed is estimated to be 250.31–267.27 mg/kg.